Pitch Angle Regulation of Floating Wind Turbines with Dynamic Uncertainty and External Disturbances - Najah F. Jasim (Iraqi Journal for Electrical and Electronic Engineering, 2015)
This paper addresses the problem of pitch angle regulation of floating wind turbines with the presence of dynamic uncertainty and unknown disturbances usually encountered in offshore wind turbines, where two control laws are derived for two different cases to continuously achieve zero pitch angle for the floating turbine. In the first case, the timevarying unknown coefficients that characterize the turbine's dynamics are assumed reasonably bounded by known functions, where robust controller is designed in terms of these known functions to achieve zero pitch angle for the turbine with exponential rate of convergence. While in the second case, the turbine's dynamics are considered to be characterized by unknown coefficients of unknown bounds. In this case, a slidingmode adaptive controller is constructed in terms of estimated values for the unknown coefficients, where these values are continuously updated by adaptive laws associated with the proposed controller to ensure asymptotic convergence to zero for the turbine's pitch angle. Simulations are performed to demonstrate the validity of the proposed controllers to achieve the required regulation objective.